Penerapan Model Pembelajaran Discovery Learning Berbantu Media Audio-Visual Pada Materi Sistem Pencernaan Manusia Dalam Meningkatkan Motivasi Belajar Siswa Di SMP Plus Darus Sholah - Rofiatul Ulfa; Laila Khusnah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
The aim of this research is to increase student learning motivation through the application of the Discovery Learning model assisted by audio-visual media on material about the human digestive system at SMP Plus Darus Sholah. This type of research is classroom action research. The research subjects were 21 students in class VIII H of SMP Plus Darus Sholah. The data analysis technique uses quantitative descriptive statistics to analyze questionnaire data. The research results show that the application of the Discovery Learning learning model through the stages of stimulation, problem formulation, data collection, data analysis, verification and generalization can increase students' learning motivation. Apart from that, increasing learning motivation can also improve student learning outcomes.